DESIGN OF BANNER DESIGN FOR ONLINE REGISTRATION FLOW FOR OUTPATIENT BPJS PATIENTS AT MUTIARA DELIMA SAWOO PONOROGO CLINIC - Alfiina Zakiyati; Rumpiati Rumpiati (Institut Kesehatan Pelamonia, 2025)
The design of a banner illustrating the online registration flow for BPJS outpatients at Mutiara Delima Sawoo Ponorogo Clinic was motivated by the continued use of manual registration, which caused long queues and confusion among patients. This study aimed to develop an informative, visually attractive, and easily understood banner to guide patients through online registration using the Mobile JKN application. The study employed a Research and Development method consisting of three stages: Define, Design, and Development. The research subjects included medical record officers, lecturers from STIKES Buana Husada, and BPJS patients as service users. Data were collected through needs identification, product design, expert validation, and user assessment. The validation results showed that the banner received very good evaluations, with a score of 95.83% from medical record officers and 91.66% from lecturers. These results indicate that the developed banner meets the required visual and informational standards for supporting patients during the online registration process. The banner also helps patients understand each registration step more clearly and effectively supports greater efficiency in outpatient registration services. In conclusion, the banner is feasible for implementation as an educational and informational medium to improve registration services and reduce patient confusion in primary healthcare facilities overall.